Percutaneous coronary interventions in patient with hemophilia A, partial gastrectomy and reccurent myocardial infarction - Vučić, Miodrag; Vacić, Nebojša (Medical Word, 2020)
Acute coronary syndrome is not rare in patients with haemophilia. We report a case of 55-year-old male patient with haemophilia A and gastric resection with Billroth II anastomosis with repeated STEMI and NSTEMI who was successfully treated by PTCA with stent implantation. Patient was admitted to the emergency department (April 2010). Coronary angiography revealed occlusion of mid-RCA, suboclusion of proximal LAD and also of medial Diagonal (Dg) brunch. Bare metal stent was implanted into the RCA. Two-years after (March 2012) patient was readmitted due to chest pain. Coronary angiography showed occluded posterior descendent artery from right coronary artery, subocluded proximal and medial LAD and first Diagonal brunch. Two Carbostents were implanted. There are no reports on the use of drug-eluting stent implantation in patients with hemophilia; however, with concerns about bleeding diathesis, bare-metal stents are regarded as safe. Our choice was new stent type, allowing more rapid reendothelialization, and minimizing the risk of stent thrombosis in the situation when the discontinuation of dual antiplatelet therapy. Antiplatelet therapy is important for preventing thrombus formation in the implanted stent even in patients with abnormal coagulation and high bleeding risk. New rapid-reendothelization stents may be the better choice in this group of patients.
Keywords: haemophilia, myocardial infarction, stent, antiplatelet therapy